Organ donation after medical assistance in dying or cessation of life-sustaining treatment requested by conscious patients: the Canadian context - Allard, Julie (Journal of medical ethics, 2017)
In June 2016, following the decision of the Supreme Court of Canada to decriminalise assistance in dying, the Canadian government enacted Bill C-14, legalising medical assistance in dying (MAID). In 2014, the province of Quebec had passed end-of-life care legislation making MAID available as of December 2015. The availability of MAID has many implications, including the possibility of combining this practice with organ donation through the controlled donation after cardiac death (cDCD) protocol. cDCD most often occurs in cases where the patient has a severe neurological injury but does not meet all the criteria for brain death. The donation is subsequent to the decision to withdraw life-sustaining treatment (LST). Cases where patients are conscious prior to the withdrawal of LST are unusual, and have raised doubts as to the acceptability of removing organs from individuals who are not neurologically impaired and who have voluntarily chosen to die. These cases can be compared with likely scenarios in which patients will request both MAID and organ donation. In both instances, patients will be conscious and competent. Organ donation in such contexts raises ethical issues regarding respect for autonomy, societal pressure, conscientious objections and the dead-donor rule. In this article, we look at relevant policies in other countries and examine the ethical issues associated with cDCD in conscious patients who choose to die.